Koneksi Database Ms. Access Dengan Macromedia Flash Menggunakan MDM Zinc - Sri Siswanti (Jurnal Ilmiah SINUS, 2011)
Flash is designed with the ability to create 2-dimensional animations that are reliable and lightweight so that the flash is widely used to establish and give effect to the animation on the website, Interactive CD and others. Good programming code that runs its own to set the animation in it or used to communicate with other programs such as HTML, PHP, and XML database approach MDM Zinc can do the scripting through flash actionscript panel which will then be combined with scripts, with MDM Zinc is an application software to directly connect to the database to generate the SWF that contains the actionscript + zinc mdm script into an EXE. Keywords : database, Flash, MDM Zinc